Systematic synthesis of phthalimide-protected unsaturated hydrazine heterocycles. Issue 13 (3rd July 2017) - Ilisson, Mihkel; Mäeorg, Uno
ABSTRACT: A four-step route for the synthesis of novel phthalimide-protected hydrazine heterocycles that include a C˭C double bond in the cycle was developed. Phthalimide-protected Boc-hydrazine was used as a starting material, which was alkylated with bromoalkenes in mild conditions. Further steps involved Boc-deprotection and second alkylation with bromoalkenes. Finally, the heterocycles were produced by ring-closing metathesis. This route allows access to these versatile building blocks without using electrophilic amination or nitrosylation, therefore, significantly reducing environmental and safety concerns. Phthalimide-protected heterocycles can be derivatized further by modifying the carbon–carbon double bond and by deprotection and subsequent functionalization of the primary amino group. During the current research, various five- to seven-membered hydrazine heterocycles and numerous novel intermediate compounds were synthesized and thoroughly characterized. GRAPHICAL ABSTRACT: